2015
DOI: 10.1523/jneurosci.5113-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Frontoparietal Network Mediates White Matter Structure Dysfunction Associated with Cognitive Decline in Hypertension Patients

Abstract: Some previous reports have suggested that hypertension is a risk factor for dementia and cognitive impairments. Using behavioral data from 1007 elderly human subjects (405 hypertensive patients) of Han ethnicity from Beijing, China, the present study aimed to assess the effects of hypertension on cognitive performance and explore related neuronal changes via advanced resting-state functional magnetic resonance imaging and diffusion tensor imaging data from 84 of these subjects (44 hypertensive patients). Cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 67 publications
12
52
0
3
Order By: Relevance
“…Although hypertension may eventually affect all of these domains, executive function is commonly affected earlier [26]. In a previous study, HPs showed declines in mainly executive function and attention compared with NPs, possibly due to the impact of white matter on executive function mediated by the frontoparietal network in the former [22]. In this study, HPs manifested mainly executive function impairment supporting this evidence indirectly, without orienting network decline.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although hypertension may eventually affect all of these domains, executive function is commonly affected earlier [26]. In a previous study, HPs showed declines in mainly executive function and attention compared with NPs, possibly due to the impact of white matter on executive function mediated by the frontoparietal network in the former [22]. In this study, HPs manifested mainly executive function impairment supporting this evidence indirectly, without orienting network decline.…”
Section: Discussionsupporting
confidence: 80%
“…Because HPs had reduced alerting network effect scores and greater difficulty resolving conflict than NPs did on POD 7 in this study, we suspect that they sustained more substantial damage to the frontal and parietal areas of the brain. Magnetic resonance imaging (MRI) studies have revealed altered patterns involving the parietal and frontal lobes in HPs relative to NPs [22]. The frontoparietal network is important for executive function, attention control, and working-memory processing [23].…”
Section: Discussionmentioning
confidence: 99%
“…The tractography differences noted between the MCI-highEF group and the MCI-lowEF group in the superior longitudinal fasciculus have been described not only in AD dementia [20], but also accompanying cognitive impairment in Parkinson’s disease and chronic hypertension. While the pathophysiology of these diseases may be different, it is important to note that differences in these regions accompany similar diminished executive changes [25, 26]. As such, it may be that a disruption in the efficiency of this tract in MCI is most indicative of whom will go on to develop dementia.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Hypertension has been suggested to impair RSFC in older adults. 28 Higher total-cholesterol levels have been associated with both lower and higher RSFC within the DMN and lower RSFC within the SAL network, 29,30 but associations have not been found in all studies. 26 VRFs might therefore reduce brain functional health, which could increase vulnerability to AD pathology and/or cognitive impairments.…”
Section: Introductionmentioning
confidence: 81%